The intra-annual variability in the performance of wave energy converters: A comparative study in N Galicia (Spain). (15th March 2015) - Carballo, R.; Sánchez, M.; Ramos, V.; Fraguela, J.A.; Iglesias, G.
Abstract: This paper presents the analysis of the intra-annual power performance of different WECs (wave energy converters) at two locations of interest in the northern coastal region of Galicia (NW Spain). With this aim, the wave resource at the locations of interest is characterised by considering a procedure whose implementation on a coastal region produces the required wave spectral information for reconstructing the coastal resource in terms of monthly characterisation matrices with the adequate resolution for conducting accurate performance computations of WECs. Next, the monthly performance of different WECs at these locations is estimated through the combination of the characterisation matrices obtained and the efficiency of the technologies analysed. The results show that the analysis of the intra-annual performance of different technologies at different locations is a key aspect so as to define the most appropriate WEC-site combination for harnessing the wave energy resource in a coastal region. Finally, the information produced by implementing the methodology considered in this work allows the reconstruction of the wave resource at any coastal site (not only at the selected locations), in the form of monthly high resolution characterisation matrices, and thus, the monthly performance of any WEC-site combination can be computed. Highlights: The intra-annual resource variability in the WECs' performance is investigated. A methodology is implemented for computing intra-annual characterisation matrices. The monthly performance of different WECs is computed at two coastal locations. The power performance could be computed at any coastal location.